2016
DOI: 10.3892/ol.2016.4198
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations of HER genes in chromophobe renal cell carcinoma

Abstract: Abstract. Chromophobe (ch) renal cell carcinoma (RCC) is the 3rd most common subtype of RCC and occurs in 5% of all RCCs. Although chRCC generally demonstrates more favorable outcomes compared with other subtypes of RCC, there is a 6-7% probability of tumor progression and metastasis in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In RCC, altered chemosensitivity mediated by 17-β-estradiol (E2) has been reported, so adjuvant therapy with E2 is possible as in other human diseases [ 24 , 45 ]. The molecular mechanisms of the action of E2 in RCC cells have been reported in recent years [ 8 , 10 , 13 , 43 , 45 ]. However, diverse genetic alterations are linked to renal cancer progression and to our ability to predict its risk [ 13 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In RCC, altered chemosensitivity mediated by 17-β-estradiol (E2) has been reported, so adjuvant therapy with E2 is possible as in other human diseases [ 24 , 45 ]. The molecular mechanisms of the action of E2 in RCC cells have been reported in recent years [ 8 , 10 , 13 , 43 , 45 ]. However, diverse genetic alterations are linked to renal cancer progression and to our ability to predict its risk [ 13 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The erbB4 gene, also known as HER4 gene, is an oncogene that encodes the fourth human epidermal growth factor receptor (HER4). Studies show that it is overexpressed in renal carcinoma and is associated with lymph node metastasis, TNM staging and postoperative survival rate of renal carcinoma (Weng et al, 2016). However, no gene annotation related to HIF-1β was found in the GO database.…”
Section: Resultsmentioning
confidence: 99%
“…chRCC is the third most common histological subtype of RCC, behind clear cell RCC and papillary RCC (3); it accounts for 5–7% of all RCC cases (4). Although patients with chRCC have a better prognosis compared with other subtypes, the long-term outcomes are highly variable and there is a 5–10% probability of eventually developing metastasis (7).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that ~64,000 new cases were diagnosed in 2017 in the USA (1), and this value has risen by 2–4% each year (2). Chromophobe RCC (chRCC) is the third most common histological subtype of RCC (3), comprising 5–7% of all RCC cases (4). Due to advances in technology for the diagnosis and treatment of chRCC, the 5-year survival rate of chRCC is >75% (5) and the outcome is typically favorable when compared with that of other subtypes (6).…”
Section: Introductionmentioning
confidence: 99%